2008
DOI: 10.1016/j.devcel.2007.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Integration of Wingless, Decapentaplegic, and Autoregulatory Inputs into Distalless during Drosophila Leg Development

Abstract: The development of the Drosophila leg requires both Decapentaplegic (Dpp) and Wingless (Wg), two signals that establish the proximo-distal (PD) axis by activating target genes such as Distalless (Dll). Dll expression in the leg depends on a Dpp- and Wg-dependent phase and a maintenance phase that is independent of these signals. Here, we show that accurate Dll expression in the leg results from the synergistic interaction between two cis-regulatory elements. The Leg Trigger (LT) element directly integrates Wg … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
139
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 97 publications
(144 citation statements)
references
References 51 publications
3
139
0
Order By: Relevance
“…Once both Dll and dac are activated, even in the same cell, we imagine that they, too, become locked into an expressed state by an autoregulatory and/or Polycomb-dependent mechanism. A recent analysis of the cis-regulatory elements controlling Dll expression in the Drosophila leg is consistent with this model (Estella et al, 2008). In particular, Dll expression in the leg disc uses two cis-regulatory elements.…”
Section: Revised Model For Pd Axis Formationmentioning
confidence: 57%
See 2 more Smart Citations
“…Once both Dll and dac are activated, even in the same cell, we imagine that they, too, become locked into an expressed state by an autoregulatory and/or Polycomb-dependent mechanism. A recent analysis of the cis-regulatory elements controlling Dll expression in the Drosophila leg is consistent with this model (Estella et al, 2008). In particular, Dll expression in the leg disc uses two cis-regulatory elements.…”
Section: Revised Model For Pd Axis Formationmentioning
confidence: 57%
“…Importantly, Brk plays a crucial role in this model because it keeps Dll switched off in a large part of the disc, thus allowing Wg-mediated activation of Dll to occur in only a small subset of the disc. Consistently, a Dll enhancer that activates expression in the young leg disc directly integrates Wg and Dpp inputs by binding Tcf, Mad and Brk (Estella et al, 2008). In addition to these inputs, there must be additional factors that limit Dll activation to ventral, but not dorsal (e.g.…”
Section: Signal Integration Into Dll and Dacmentioning
confidence: 98%
See 1 more Smart Citation
“…As mentioned in previous sections, this gene contains cis-regulatory elements, able to work in isolation, that are active in D. melanogaster leg discs. These regulatory elements are separated by 12 Kb of DNA without enhancer activity in leg discs (Estella et al, 2008). A recent study revealed that at least four different regions within these 12 Kb harbor functional binding sites for the transcription factor GAF ( Fig.…”
Section: The Unknown Spatial Distribution Of Cis-regulatory Informationmentioning
confidence: 99%
“…In this organ, part of the expression pattern of the gene Distalless (Dll) is controlled by two distant enhancers named LT and M. These two enhancers drive very different expression patterns, and none of them alone recapitulates Dll native expression in the leg disc (Estella et al, 2008). However, when these two elements are combined in a lacZ reporter construct, the enhancer duo drives expression in all Dll-expressing cells (Estella et al, 2008). A similar behavior has been observed in the gene sloppy-paired-1 during Drosophila embryonic development (Prazak et al, 2010).…”
Section: Developmental Dynamicsmentioning
confidence: 99%